Health and Safety Analysis for Fisherman in East Surabaya, Indonesia - Santi Frestiqauli; Daniel Mohammad Rosyid; Wimala Lalitya Dhanistha; Anita Kusuma Wardhani; Shade Rahmawati; Madea Eka Silfiani (International Journal of Offshore and Coastal Engineering, 2026)
The number of fishermen in Indonesia has continued to decline in the last decade as reported by the Statistics of Marine and Coastal Resources 2021. In 2010 the number of fishermen was recorded at 2.16 million people. But in 2019, the number was recorded at only 1.83 million people. Thus, there was a decrease in the number of fishermen by 330,000 people in 2010-2019. The fisheries sector is one of the most dangerous industries. In contrast, the health and safety of the people, especially fishermen are too far below occupational health and safety feasibility standards. This research used job safety analysis method for hazard identification and risk assessment for fisherman activities during preparation, operation, and pasca-operation. Data were collected through observation and interview 30 fishermen in East Surabaya. Results of observations divided by three activities shows that fishermen don’t prepare themselves with safety kit or safety equipment, including for personal protective equipment. The conclusion is most potential hazards could be minimized by using personal protective equipment. To minimize the risk of fatality, fishermen should carry a first aid kit, and communication devices and should be accompanied when going to sea. There are future research and program to increase fisherman awareness prior to safety.